Evolution of legal regulation of corporate agreement in domestic legal system - Ніколенко, М. О. (НДІ ПЗІР НАПрН України, 2018)
The article is devoted to the evolution of legal regulation of corporate agreements in Ukraine. The attention has been paid to the development of corporatisation in the imperial and soviet times as a prerequisite for the slow and long-term implementation of the corporate agreements institute in the domestic legislation regulating business entities activity. The stages of legal comprehension of corporate agreements have been outlined. The prospects of scientific researching of the mentioned institute in the domestic legal system and the doctrine of economic law have been defined.
Keywords: corporate agreement; corporatization; corporate rights; joint-stock companies; agreement on realization of rights of participants (founders) of a partnership; shareholders agreement